Standardised step by step approach to adnexectomy by Vaginal Natural Orifice Transluminal Endoscopic Surgery. (July 2022) - Baekelandt, J.; Noori, N.; Hofmann, L.; Mansoor, A.; Kapurubandara, S.
Abstract: Vaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES) combines the advantages of vaginal surgery with those of laparoscopic surgery. Feasibility of vNOTES for other indications such as hysterectomy, ovarian cystectomy and myomectomy has been established. In this article, we describe a standardised step by step process to perform adnexal surgery by vNOTES.